2020
DOI: 10.1371/journal.pone.0231841
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological and pharmacokinetic profile of the novel ocular hypotensive prodrug CKLP1 in Dutch-belted pigmented rabbits

Abstract: Elevated intraocular pressure is the only treatable risk factor for glaucoma, an eye disease that is the leading cause of irreversible blindness worldwide. We have identified cromakalim prodrug 1 (CKLP1), a novel water-soluble ATP-sensitive potassium channel opener, as a new ocular hypotensive agent. To evaluate the pharmacokinetic and safety profile of CKLP1 and its parent compound levcromakalim, Dutch-belted pigmented rabbits were treated intravenously (0.25 mg/kg) or topically (10 mM; 4.1 mg/ml) with CKLP1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Stumpff et al [ 49 ] demonstrated effluxion of K via maxi-K channels could result in trabecular meshwork relaxation. Study has shown that pharmacologic openers of functional K dependent ATP (K ATP ) channel lower the intraocular pressure in normotensive animal models and nonhuman primates [ 50 , 51 ]. The alteration of K current may activate the cell volume regulation in trabecular meshwork that obstructed aqueous humor outflow and further resulted in increased intraocular pressure [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Stumpff et al [ 49 ] demonstrated effluxion of K via maxi-K channels could result in trabecular meshwork relaxation. Study has shown that pharmacologic openers of functional K dependent ATP (K ATP ) channel lower the intraocular pressure in normotensive animal models and nonhuman primates [ 50 , 51 ]. The alteration of K current may activate the cell volume regulation in trabecular meshwork that obstructed aqueous humor outflow and further resulted in increased intraocular pressure [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“… 15 The ocular hypotensive properties of topical K ATP channel openers, including levcromakalim, diazoxide, and nicorandil, have been described in human anterior segments and multiple normal and ocular hypertensive animal models. 16 20 Studies using knockout mouse models treated with subtype-specific K ATP channel openers have strongly indicated that the ocular hypotensive effect appears to occur through K ir 6.2/SUR2B subunit-containing channels. 19 When applied topically to the eye, K ATP channel openers such as cromakalim prodrug 1 (CKLP1) have been demonstrated to lower IOP by specifically reducing episcleral venous pressure.…”
mentioning
confidence: 99%
“… 21 After topical application to the eye, endogenous phosphatases cleave the phosphate group converting CKLP1 to the active metabolite levcromakalim. 16 , 21 , 22 CKLP1 was shown to retain the potent ocular hypotensive properties of levcromakalim and showed additive effects when used in combination with existing IOP-lowering drugs in normotensive animal model systems. 16 , 17 , 21 , 22 …”
mentioning
confidence: 99%
See 1 more Smart Citation